1998
DOI: 10.1097/00005768-199808000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Improved running economy following intensified training correlates with reduced ventilatory demands

Abstract: Recreational runners can improve RE and aerobic run performance by exchanging parts of their conventional aerobic distance training with intensive distance or long-interval running, whereas short-interval running is less efficient. The improvement in RE may relate to reduced ventilatory demands. Muscle fiber type distribution was unaltered with training and showed no associations with RE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
70
0
5

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(84 citation statements)
references
References 30 publications
9
70
0
5
Order By: Relevance
“…Additionally, 24 weeks of low-volume and high-volume resistance exercise-based circuit training is capable of improving measures of muscular strength, power, and endurance, including 1RM bench press and leg press, vertical jump power, and bench press and leg press repetitions to failure at 80% 1RM (Marx et al, 2001). Given that CrossFit incorporates elements of metabolic conditioning including both aerobic and anaerobic, as well as resistance-based training in combination, it is likely that chronic training would lead to similar improvements in aerobic power, anaerobic capacity, and muscular fitness as seen by Tabata et al and Franch et al (Franch et al, 1998). In addition, CrossFit may lead to improved markers of metabolic health, given that shorter and intense exercise bouts similar in nature to CrossFit training have been shown to elicit positive effects on symptoms associated with cardiometabolic diseases such as coronary heart disease (Gibala, …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, 24 weeks of low-volume and high-volume resistance exercise-based circuit training is capable of improving measures of muscular strength, power, and endurance, including 1RM bench press and leg press, vertical jump power, and bench press and leg press repetitions to failure at 80% 1RM (Marx et al, 2001). Given that CrossFit incorporates elements of metabolic conditioning including both aerobic and anaerobic, as well as resistance-based training in combination, it is likely that chronic training would lead to similar improvements in aerobic power, anaerobic capacity, and muscular fitness as seen by Tabata et al and Franch et al (Franch et al, 1998). In addition, CrossFit may lead to improved markers of metabolic health, given that shorter and intense exercise bouts similar in nature to CrossFit training have been shown to elicit positive effects on symptoms associated with cardiometabolic diseases such as coronary heart disease (Gibala, …”
Section: Discussionmentioning
confidence: 99%
“…This finding is similar to investigations of other forms of high-intensity interval-type training and resistance exercise-based circuit training that have resulted in improved measures of fitness (Laursen & Jenkins, 2002). Franch et al (Franch, Madsen, Djurhuus, & Pedersen, 1998) showed that 6 weeks of intense interval training using 4 to 6 sets of 4 minute intervals resulted in a 6% improvement in VO2max and a greater increase in time to exhaustion at 85% VO2max compared to 6 weeks of continuous running (+93% vs. +67%, respectively). Similarly, Tabata et al reported a 7 ml/kg/min increase in VO2max in addition to a 28% increase in anaerobic capacity following 6 weeks of 7 to 8 sets of 20 second cycling at ~170% VO2max with a 10 second rest period between bouts while 6 weeks of sustained moderate-intensity exercise resulted in a 5 ml/kg/min increase in VO2max, but no increase in anaerobic capacity.…”
Section: Discussionmentioning
confidence: 99%
“…The trainability of running economy, however, is uncertain. Some studies have shown that training volume significantly improved running economy 19,[39][40][41] , while other studies have shown no improvement 7,42 .…”
Section: Discussionmentioning
confidence: 99%
“…The trainability of running economy, however, shows conflicting results. Some studies have shown that training volume significantly improved running economy 26,35,50,51 , while other studies have shown no improvement 52,53 .…”
Section: Training Volumementioning
confidence: 99%